Parallel paths to constructivism : Jean Piaget and Lev Vygotsky - Pass, Susan (Emerald Publishing Limited : Information Age Pub., 2004)
No two people were more responsible for the current way lessons are taught worldwide than Jean Piaget and Lev Vygotsky. Both men had an important impact worldwide on how a person should be taught--starting in the last century and continuing today. Jean Piaget's Genetic Epistemology concentrated on the individual in learning. Lev Vygotsky's Cultural-Historical Theory concentrated on the social in learning. All over the world, teachers today use each man's ideas. Some use them at different times in their classrooms and others have learned to use them combined into the same lesson--bringing us to the crux of this book; namely, there are many lessons to learn by discovering the dynamics in the lives of both men. While both were from very different countries, there are many similarities in their lives. While most professors teaching introductory educational psychology courses focus on the difference in their lesson strategies, there are some remarkable similarities between their respective pedagogies.